Effects of doxorubicin administration on bone strength and quality in sedentary and physically active Wistar rats. Issue 12 (December 2016) - Fonseca, H.; Carvalho, A.; Esteves, J.; Esteves, V.; Moreira-Gonçalves, D.; Duarte, J.
Abstract Summary Doxorubicin (DOX) is used in pediatric cancer treatment. This study assessed the effects of 7 weeks of DOX and 10-week recovery on bone quality and biomechanical properties in sedentary and exercised Wistar rats. DOX decreases femur diaphysis radial growth and biomechanical properties. Some of these DOX effects were aggravated by exercise. Introduction Bone growth in pre-pubertal years critically influences adult fracture risk. DOX is widely used in the treatment of pediatric cancers, but there is limited evidence on its potential negative effects on bone growth. Exercise improves bone growth in children, but there is no evidence if it protects against DOX-induced bone toxicity. This study investigates the early and intermediate effects of a 7-week course of DOX on bone histomorphometry and strength in sedentary and exercised growing animal models. Methods Sixty-eight male Wistar rats (8 weeks) were treated with DOX (2 mg kg−1 ) or vehicle for 7 weeks and afterward housed in standard cages or in cages with a running wheel and killed 2 or 10 weeks after last DOX administration. Femurs and blood were collected for assaying geometry, trabecular microarchitecture (histology), biomechanical properties (three-point bending and shearing of the femoral neck), bone calcium content and density (atomic absorption spectroscopy), and bone turnover markers (ELISA). Results DOX treatment reduced the femur diaphysis radial growth, with DOX-treated animals having a lower tissue area, cortical area, cortical thickness, and moment of inertia. DOX also decreased distal femur trabecular bone volume and trabecular number and increased trabecular separation. Femur diaphysis stiffness and maximum load were also reduced in past DOX-treated animals. Exercise was shown to worsen the effects of past DOX treatment on the femur diaphysis mechanical properties. Conclusion DOX negatively affects bone geometry, trabecular microarchitecture, and femur mechanical properties in growing Wistar rats. Exercise further aggravates the detrimental effects of past DOX treatment on bone mechanical properties.